In silico studies and β-cyclodextrin mediated neutral synthesis of 4-oxo-4, 5, 6, 7-tetrahydroindoles of potential biological interest. Issue 24 (11th June 2020) - Dhananjaya, G.; Rao, A.V. Dhanunjaya; Hossain, Kazi Amirul; Anna, Venkateswara Rao; Pal, Manojit
Graphical abstract: Highlights: First β -cyclodextrin ( β -CD) mediated synthesis of 4-oxo-4, 5, 6, 7-tetrahydroindoles in water was achieved. The synthesis involved a 3-component reaction under neutral conditions. Few tetrahydroindoles showed chorismate mutase inhibition in vitro . Abstract: Prompted by the in silico docking study predictions the first β-cyclodextrin (β-CD) mediated synthesis of 4-oxo-4, 5, 6, 7-tetrahydroindoles in water was achieved via a 3-component reaction under neutral conditions. A range of compounds was prepared by using this environmentally friendly method in good yields (82–92%). The catalyst β-CD could be recovered and recycled. The in silico docking studies predicted chorismate mutase (CM) inhibitory properties of some of the tetrahydroindoles synthesized that was supported by the results of subsequent in vitro assay.